Identification of morphological indices of physiological maturity in soybean (Glycine max) genotypes - Gontia, A S; Nigam, P K; Sonakia, V K; Dwivedi, S K (The Indian Journal of Agricultural Sciences, 2012)
An experiment was conducted during rainy season of 1992 and 1993 to identify the morphological indices of seed maturation and physiological maturity in 10 genotypes (’Punjab 1’, ’Ankur’., ’JS 75-46’, ’JS 78-80’. ’JS 79-81’, ’JS 81-303’, ’JS 81-607’, ’JS 81- 335’, ’JS 81-1625’ and ’PK 472’) of soybean [Glycine max (L.) Merr.]. All the genotypes reached the physiological maturity by 56 days after anthesis accompanied with higher dry weight of seed (83.05%), dry weight of plant (18.73 g/plant), seed index (10.39 g), germinability (88.4%) and seedling vigour (7.06 cm seedling length and 0.081 g dry weight). In all the genotypes seed and pod volumes (0.021 ml and 0.10 ml) were maximum at 49 days after anthesis. At physiological malurity 4-10.66 leaves/plant were retained hy the genotypes and colour of the pod and stem became dark redÂ·brown to brown. The seeds collected at 35 days after anthesis did not germinate.